The Labor Market Effects of Pregnancy Accommodation Laws - Emily Battaglia; Jessica H. Brown (Institute of Labor Economics (IZA), 2025)
Pregnancy accommodation laws require "reasonable accommodations" for pregnant workers, i.e., sitting down, lifting restrictions, and additional bathroom breaks. Although these laws may make it easier for women to remain employed during pregnancy, as a mandated benefit, they may also discourage employers from hiring employees who may become pregnant. We estimate the effect of pregnancy accommodation laws on labor market outcomes for women of childbearing age in order to determine whether these laws lead employers to discriminate against young women in hiring. Using a triple differences design comparing women's and men's labor market outcomes throughout the staggered roll-out of thirteen pregnancy accommodation laws from 2013 to 2016, we find no overall impact on female employment and wages. Under some specifications, we find women are more likely to choose occupations where physical abilities are important, suggesting possible increased accessibility. For subgroups more likely to be impacted - those with less education, in more physically-intense occupations, and married without children - we do find modest declines in earnings and employment. That the burden falls on both suggests women value the benefit but at less than it costs to provide.
Keywords: K31; J32; I18; 330; pregnancy accommodations; mandated benefits